2020
DOI: 10.1002/rco2.10
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐targeted treatment approach to cancer cachexia: Auckland's Cancer Cachexia evaluating Resistance Training (ACCeRT) trial

Abstract: Background Cancer cachexia is a condition often seen at diagnosis, throughout anti‐cancer treatments and in end‐stage non‐small‐cell lung cancer patients. Methods and results Participants with late‐stage non‐small‐cell lung cancer and cachexia (defined as ≥5% weight loss within 12 months) were randomly assigned 1:2 to 2.09 g of eicosapentaenoic acid (EPA) and 300 mg of cyclo‐oxygenase‐2 inhibitor celecoxib orally once daily vs. same dosing of EPA, celecoxib, plus two sessions per week of progressive resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Consistent with this, using a resistance training program, signifcant improvements were obtained in the 6-minute walk test and the sit-stand test, and the lean mass of the lower extremities, as well as knee extensor strength, were increased, realizing that three months of training in patients with cachexia induced by pancreatic cancer led to a delay in the appearance and progression of cachexia in cancer patients, represented by an increase in lean mass compared to the control group [45]. Within the same scope, Rogers et al demonstrated that the application of progressive resistance training to counteract the loss of fat and muscle mass was feasible and highly acceptable for cancer patients [46].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, using a resistance training program, signifcant improvements were obtained in the 6-minute walk test and the sit-stand test, and the lean mass of the lower extremities, as well as knee extensor strength, were increased, realizing that three months of training in patients with cachexia induced by pancreatic cancer led to a delay in the appearance and progression of cachexia in cancer patients, represented by an increase in lean mass compared to the control group [45]. Within the same scope, Rogers et al demonstrated that the application of progressive resistance training to counteract the loss of fat and muscle mass was feasible and highly acceptable for cancer patients [46].…”
Section: Resultsmentioning
confidence: 99%
“…A trimodal approach is usually the preferred treatment studied in this population, which includes a combination of exercise, nutritional supplementation, and nonsteroidal anti-inflammatory drugs. The study ACCeRT was a small prospective trial in which 20 adult patients with non-small-cell lung cancer (NSCLC) and refractory cachexia were randomized to receive EPA and celecoxib or EPA, celecoxib, essential amino acids, and RT [ 85 , 86 ]. Interventions in both arms were feasible, and stabilization of body weight and free fat mass could be obtained for some weeks with both approaches [ 85 ].…”
Section: Multimodal Approach In Cachexiamentioning
confidence: 99%
“…The study ACCeRT was a small prospective trial in which 20 adult patients with non-small-cell lung cancer (NSCLC) and refractory cachexia were randomized to receive EPA and celecoxib or EPA, celecoxib, essential amino acids, and RT [ 85 , 86 ]. Interventions in both arms were feasible, and stabilization of body weight and free fat mass could be obtained for some weeks with both approaches [ 85 ]. In Pre-MENAC, a phase II trial with NSCLC and pancreatic cancer patients, celecoxib associated with EPA-enriched supplements and physical exercise (RT and ET) was a safe and viable intervention for pre-cachectic and cachectic individuals [ 87 ].…”
Section: Multimodal Approach In Cachexiamentioning
confidence: 99%
“…Trends in efficacy, in terms of improvement and/or stability in cachexia markers, were seen within magnetic resonance imaging (MRI) muscle volume, albumin, and C-reactive protein (CRP) levels within both arms. 14 Participants who had completed the ACCeRT main study could continue with medication and/or exercise sessions post end of the main study under compassionate use (CU). Data on the ongoing acceptability, compliance and safety of this multi-targeted regimen in refractory cachectic NSCLC patients will be used to calculate the power and number of participants required for a future phase II study.…”
Section: Introductionmentioning
confidence: 99%